Emma Goldman and the Russian Revolution : From Admiration to Frustration - Jacob, Frank 1984- (De Gruyter, 2020)
How did Emma Goldman perceive the Russian Revolution and how did her perception change between 1917 and the early 1920s? What impact did the revolution’s corruption by Lenin have on the anarchist’s perception and what made her change her mind, going from defending the Russian Revolution to becoming a crusader against Bolshevism?